Ethics and sustainability in global supply chain management - Akkucuk, Ulas, 1975- (Advances in logistics, operations, and management science (ALOMS) book series., 2017)
"Various industries in modern society can contribute to many different sustainable development initiatives. By implementing better processes for resource usage and its impacts, businesses can play a vital role in creating a cleaner environment. Ethics and Sustainability in Global Supply Chain Management is a comprehensive reference source for the latest scholarly material on organizational procedures and methods that ensure environmental sustainability, while maintaining effective production processes. Highlighting the most innovative topics and perspectives, such as life cycle costing, waste management, and business leadership, this book is ideally designed for professionals, academics, practitioners, graduate students, and researchers interested in developing green supply chain processes"- Resumé vydavatel